S120 Gene therapy for pulmonary alveolar proteinosis. (15th November 2017) - Atsumi, N; Pilou, A; Pringle, I; Ashworth, RC; Meng, C; Chan, M; Gill, DR; Hyde, S; Morgan, C; Alton, EWFW; Griesenbach, U
Abstract : Introduction: Pulmonary alveolar proteinosis (PAP) is characterised by accumulation of surfactant in the terminal airways. Granulocyte-Macrophage Colony-Stimulating-Factor (GM-CSF) stimulates alveolar macrophages to clear surfactant. The presence of GM-CSF autoantibodies in autoimmune PAP (aPAP) leads to surfactant build-up and impaired gas exchange. This causes respiratory symptoms and can ultimately be fatal due to hypoxaemic respiratory failure. We hypothesise that lentivirus-mediated gene transfer of GM-CSF may be suitable to treat aPAP and propose to assess efficacy of GM-CSF gene transfer in GM-CSF knockout mice, which recapitulate aPAP lung disease. The murine GM-CSF (mGM-CSF) cDNA was cloned into a lentiviral vector, which was pseudotyped with the F and HN proteins from Sendai virus to enable efficient lung transduction (rSIV.F/HN-mGM-CSF). Methods and Results: To confirm if the vector produces mGM-CSF we first transduced A549 cells with multiplicity of infection (MOI) of 0.1–100 (n=6/group). 48 hours after transduction dose-related mGM-CSF expression was confirmed in the medium. We next assessed whether the mGM-CSF produced after gene transfer was biologically active by comparing the proliferation rate of FDC-P1 cells, a mGM-CSF-dependent mouse myeloid progenitor cell line, in the presence of gene therapy- produced mGM-CSF (0.001–10 ng/ml) and purchased recombinant mGM-CSF protein (n=6/group). The dose-related proliferation rates in both conditions were similar (figure 1 ss). In preliminary experiments, we next assessed whether gene transfer led to GM-CSF production in vivo . rSIV.F/HN-mGM-CSF (1e7 transduction units (TU)/mouse) was administered to wild-type mice by nasal "sniffing". Control mice remained untransduced (n=3/group). mGM-CSF levels were quantified in lung tissue homogenate and broncho-alveolar lavage fluid (BALF) 14 days after gene transfer. mGM-CSF levels in untreated mice were below the limit of detection of the ELISA, but high levels of mGM-CFS were detectable in lung tissue (median 825 (range 460–3790) pg/mg) and BALF (median: 3330 (range 2307–7958) pg/ml). Conclusion: rSIV.F/HN-mGM-CSF produced mGM-CSF in vitro and in vivo . The biological function of the protein was confirmed in vitro and evaluation of mGM-CSF gene transfer efficacy in murine aPAP model is ongoing.